Drug injection in Iranian prisons: evidence from the National Rapid Assessment and Response (RAR) survey, 2017. (4th May 2022) - Karimi, Salah Eddin; Vameghi, Meroe; Roshanfekr, Payam; Ahmadi, Sina; Ali, Delaram; Higgs, Peter
ABSTRACT: Objective: In this rapid assessment and response (RAR) survey, the demographic and behavioral differences between two sub-groups of people with incarceration histories are described. Data from those who report injecting in prison and those who do not were analyzed. Methods: Analysis of data from a sub-set of 1, 240 participants recruited to a RAR national survey and reporting a history of incarceration. Results: The prevalence of ever drug injecting in prison was 15.08% (N = 187, CI: 13.3–17.4). Participants with only primary school education were more likely to report injecting ( p < .001), were more frequently imprisoned ( p < .001) and reported having never heard about HIV ( p < .001). The multivariable logistic regression model showed that participants who reported injecting in prison were different in terms of their education (never attending school, OR = 2.29, 95% CI: 1– 5.23) and the number of times they had been in prison (> twice OR = 1.96, 95% CI: 1.15– 3.29). Conclusions: Identifying the factors influencing injection drug use in prison can help design effective strategies to prevent harms in vulnerable prisoners. Alternatives to prison for people who use drugs require further consideration in Iran.